High Performance Liquid Chromatography Determination of Formitol - Foroughifar, N.; Mobinikhaledi, A.; Tajbakhsh, M.; Naeimi, H. (Asian Journal of Chemistry, 2010)
Formitol, industrial or synthetic polyols, is prepared commercially by the catalytic hydrogenation of formose solution. High performance liquid chromatography was used for separation and identification of polyols, which are available in synthesized formitol. Polyols such as sorbitol (retention time = 13.01 min), glycerol (retention time = 15.44 min), ethylene glycol (retention time = 17.18 min) were the major polyhydroxy compounds in formitol which were analyzed by HPLC technique.